2012
DOI: 10.1016/j.tetlet.2011.11.124
|View full text |Cite
|
Sign up to set email alerts
|

New indole trimers as precursors for molecular electronic materials

Abstract: We thank the University of Edinburgh for funding and the EPSRC and JST for support of the UK-Japan collaboration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…[32] Similar results were obtained by the Ruiz group; they showed that by lowering the symmetry of triindole, its photophysical and electronic properties can be tuned significantly, and also there is an improvement in fluorescence quantum yield. [33] Du et al showed that TN is rich in electronic character and electron delocalization than T. [34] Both the above-studied molecules T and TN are planar π-extended electron-rich molecules, which make these molecules have great potential application in DSSCs, [35] field-effect transistors (FETs), [36] OLEDs, [37,38] two-photon absorption (TPA), [39] and organic laser and fluorescent sensors. [33,40] Other analogs of T are oxatruxene (TO), silatruxene (TSi), and thiatruxene (TS), which are also synthesized, and their photophysical properties (except TS) are reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…[32] Similar results were obtained by the Ruiz group; they showed that by lowering the symmetry of triindole, its photophysical and electronic properties can be tuned significantly, and also there is an improvement in fluorescence quantum yield. [33] Du et al showed that TN is rich in electronic character and electron delocalization than T. [34] Both the above-studied molecules T and TN are planar π-extended electron-rich molecules, which make these molecules have great potential application in DSSCs, [35] field-effect transistors (FETs), [36] OLEDs, [37,38] two-photon absorption (TPA), [39] and organic laser and fluorescent sensors. [33,40] Other analogs of T are oxatruxene (TO), silatruxene (TSi), and thiatruxene (TS), which are also synthesized, and their photophysical properties (except TS) are reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Our initial step was to find a convenient method for the trimerization of 1 H ‐indole‐6‐carboxylic acid ethyl ester (Scheme ). Trimerization of some substituted indoles has previously been reported . After modifying the reported conditions, Et 3 tat was successfully synthesized by the reaction of 1 H ‐indole‐6‐carboxylic acid ethyl ester with Br 2 in presence of excess formic acid.…”
Section: Resultsmentioning
confidence: 99%
“…Trimerization of some substituted indoles has previously been reported. [19] After modifying the reported conditions, Et 3 tat was successfully synthesized by the reaction of 1H-indole-6-carboxylic acid ethyl ester with Br 2 in presence of excess formic acid. The product was obtained directly by precipitation from the reactionm ixture in acceptable purity,a ss hown by 1 HNMR spectroscopy.T his compound was then hydrolyzed to obtain the parent triazatruxene ligand,H 3 tat.…”
Section: Resultsmentioning
confidence: 99%
“…Some TATs can behave as twophoton absorption chromophores, [8] can generate electroactive discotic liquid crystals, [9] and have been tested in organic fieldeffect transistors (OFETs). [10] Reported applications of TATs include the development of bulk heterojunction solar cells, [11] organic light-emitting diodes (OLEDs), [12] and sensing devices. [13] In this paper we report: the synthesis, separation, and comparative characterization of eumelanin-inspired symmetric and asymmetric TATs prepared from 5,6-dimethoxyindole (1 a and 2 a), 5,6-dibenzyloxyindole (1 b,c and 2 b,c), and 6-hydroxyindole (1 d and 2 d); a detailed characterization of their optoelectronic properties with the support of quantum chemical calculations based on TD-DFT; preliminary evidence of self-assembly behavior in solution; the applications of these TATs as emitting materials in OLED devices.…”
Section: Introductionmentioning
confidence: 99%